Exploring the Unseen: Muslim Students' Journeys in Catholic Religious Education Classes - Arjie B. Barihasion; Grace Mae Donque; Nica Leslie Mediana; Alfer Jann Tantog; Rovelyn CerdiÃ±a (Millah: Journal of Religious Studies, 2023)
Muslim students who attend Catholic institutions engage with Catholic religious education classes by bringing a variety of narratives to the fore. The aim of this study employs how these students contribute diverse narratives to the classroom, which intertwine with a range of challenges and struggles. Through an in-depth examination of the experiences of ten (10) participants enrolled in Catholic institutions, the researchers employ qualitative research techniques, including interviews and verbatim transcriptions. They identify significant patterns, behaviors, and distinguishing characteristics essential to the case's setting through a careful categorizing procedure. Positive experiences, such as a sense of happiness and inclusion, fostering interfaith connections, and promoting a broader comprehension of Catholic religious beliefs and practices, emerge from the findings. Conversely, negative encounters, including unmet accommodation needs, challenges in understanding unfamiliar doctrines, academic struggles, and limited class participation, prompt the development of coping strategies. The findings of this study offer valuable insights for educators, school administrators, and policymakers within Catholic institutions. By recognizing and addressing the challenges encountered by Muslim students, these results foster the establishment of learning environments that are inclusive and provide meaningful support. Moreover, the study underscores the importance of interfaith dialogue within educational settings, contributing to a more harmonious and enriching experience for all students involved.